Online or Face-to-Face: Do Mission-Related Student Learning Outcomes Differ?. Issue 3 (27th May 2019) - Lang, Charlotte S.; Holzmann, Gwetheldene; Hullinger, Hallett; Miller, Mary Lou; Norton, Timothy D.
Abstract: This study investigated how an authentic assessment program was used to examine student learning outcomes within the context of a Christian university's institutional mission, core values, and distinctive qualities. For the purposes of this study, an authentic assessment program is defined as assessing student-produced work within the context of the institutional mission. A sample of 1, 814 undergraduate students taking one or more general education courses at the university during the 2007–2009 academic years was examined for any significant differences in student learning outcomes. A univariate analysis of covariance (ANCOVA) indicated the Student Assessment System (SAS) scores for the online students were not significantly different from the SAS scores for the face-to-face (F2F) students after controlling for course grade. These results suggest that online students achieved the same critical mission-related educational outcomes that the university required of its F2F students. An implication of this finding is that the university just as effectively articulated its faith-based mission and vision to the online students as it did to its students taking classes F2F.